Analysis of intense dust storms over the eastern Mediterranean in March 2018: Impact on radiative forcing and Athens air quality. (15th July 2019) - Kaskaoutis, D.G.; Dumka, U.C.; Rashki, A.; Psiloglou, B.E.; Gavriil, A.; Mofidi, A.; Petrinoli, K.; Karagiannis, D.; Kambezidis, H.D.
Abstract: This study examines the multiple dust storms that hit the eastern Mediterranean and Greece during March 2018, emphasizing on the atmospheric dynamics for their generation, the source regions, the dust-induced radiative forcing and the impacts on PM concentrations in Athens. In March 2018, several dust storms facilitated by increased cyclonicity in the western Europe/Mediterranean and by the Sharav cyclogenesis along the north African coast resulted in abnormal-high columnar aerosol loading and PM concentrations over Greece. The dusty days were associated with intense winds (>15 - 20 ms −1 ) from southwestern directions, triggered by cyclonic circulations over the central/eastern Mediterranean and troughs over Italy and the north African coast. Statistical analysis of the backward air-mass trajectories shows that the highest PM10 concentrations are related to dust sources in Libya, while Ceilometer profiles indicate thick dust plumes with highest intensity between the surface and 3 km over Athens. The monthly-averaged hourly PM10 concentrations at several stations in the Athens basin ranged from 37 μgm −3 to 53 μgm −3, while nine days exhibited PM10 daily-means above 50 μgm −3, characterized as dusty days. The PM10 concentrations in Athens maximized on 25–26 March (∼500 μgm −3 at hourly basis), while the PM2.5 constitutes 38%–59% of PM10, indicating a dominance of coarse particles. Aerosol radiative forcing (ARF) estimates via the synergy of OPAC and SBDART models at three AERONET stations in Greece revealed significant impact of dust on radiation budget, with large (∼−40 W m −2 to −50 W m −2 ) decrease in surface solar radiation and an overall cooling effect at the top of atmosphere (∼−5 to −30 W m −2 ). The atmospheric heating via the dust-aerosol absorption results in heating rates of ∼0.5 K day −1 . Graphical abstract: Image 1 Highlights: Several intense dust storms over the East Mediterranean in March 2018. Cyclone-induced dust storms, gale Khamsin winds. High PM10 concentrations (>400 μgm −3 ) in Athens. Thick dust plumes from surface up to 4 km over Greece.